ESTIMATING FLOW DISCHARGES IN SMALL STREAMS BY USING HYDROLOGIC MODEL A CASE STUDY BATMAN BASIN IN TURKEY - Yuksel, Ibrahim; Demirel, Ibrahim Halil (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2021)
Utilizing the potential of rivers for energy, irrigation and water supply is possible with the design of the structures to be built, and measured flow data are needed for planning. However, the flow data of small streams are not known, generally because there are no flow observation stations in sub-basins. One of the software developed to predict flow data in small streams is the Hydrologic Engineering Center Hydrologic Modelling System (HEC-HMS). In the model, the parameters of the proxy basins that have a flow observation station are calibrated and transferred to the sub-basins where the flow will be estimated. In this study, the flow data of eight sub-basins without observation stations within the borders of Batman province were estimated with Baskoy and Celebiyan parameters selected as proxy basins. The flow data estimated from the model were compared with the measurements obtained from the floats and pitot tube methods, which are the flow discharge estimates based on the velocity measurement, which are theoretical methods. The simulated values of the proxy basin flows are evaluated using the Nash Sutcliffe (NSE) and. Relative Volume Error (RVE) criteria. Calibration (Baskoy NSE=84%, RVE=-24%; Celebiyan NSE=72%, RVE=9.7%) and verification (Baskoy NSE=83%, RVE=-14%; Celebiyan NSE=71%, RVE=0.65%) shows that the measured basin flow and peak flows for periods can be estimated as well as possible. When the results and suggestions obtained from this study are put into practice, significant contributions will be made to the national economy by ensuring efficient use of all small rivers in other basins, particularly the Batman basin.
Keywords: Small stream; Flow discharge; Watershed modelling system; Hydrologic model; Batman basin; Turkey; HEC-HMS; RUNOFF SIMULATION; CURVE NUMBER; RAINFALL; PREDICTIONS; CATCHMENT; Environmental Sciences & Ecology